2007
DOI: 10.1016/j.still.2007.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different management practices on the soil–water balance and crop yield for improved dryland farming in the Chinese Loess Plateau

Abstract: Field experiments were carried out to study the effects of different soil management practices on the water balance, precipitation use efficiency (PUE), and crop yield (i.e. winter wheat and peanut) on a loess soil near Luoyang (east edge of the Chinese Loess Plateau, Henan Province, China). Field plots were set up in 1999 including following soil management practices: subsoiling with mulch (SS), no-till with mulch (NT), reduced tillage (RT), two crops per year (i.e. winter wheat and peanut, TC), and a convent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
63
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(75 citation statements)
references
References 21 publications
11
63
1
Order By: Relevance
“…In farmland, tillage activities usually break down the normal structure and loosen the structure of topsoil, decreasing soil bulk density (Jin et al, 2007), which in turn increases the rain-water infiltration capacity and increases soil moisture in shallow layers (Wang et al, 2009a). In this study, as shown in Table 2 and Fig.…”
Section: Effects Of Landscape Management On Soil Moisturementioning
confidence: 99%
“…In farmland, tillage activities usually break down the normal structure and loosen the structure of topsoil, decreasing soil bulk density (Jin et al, 2007), which in turn increases the rain-water infiltration capacity and increases soil moisture in shallow layers (Wang et al, 2009a). In this study, as shown in Table 2 and Fig.…”
Section: Effects Of Landscape Management On Soil Moisturementioning
confidence: 99%
“…However, wheat productivity is seriously curtailed by water shortage and nutrient deficiency as a result of severe water loss (such as evaporation, surface runoff, and downward movement) and soil erosion (Jin et al 2007). Different kinds of mulch have been used to conserve soil water in these areas (Li et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Maybe the soil erosion from rainfall during summer fallow resulted in the low available K in the treatment C. Due to the continental monsoon climate of this region, more than 60% of the annual precipitation falls during the wheat fallow period (Jin et al, 2007). In this study, the available K of five layers of all the treatments was decreased after wheat harvest compared to them before wheat sowing (data not shown).…”
Section: Soil Available Kmentioning
confidence: 63%
“…More than 60% of the annual precipitation falls on this area when wheat fields are fallow (usually from July to September) because of the continental monsoon climate (Jin et al 2007). Tang (2004) stated that severe wind and water erosion, unsuitable cultivation systems, and a serious lack of organic fertilizer lead to soil quality degradation, fragile physical structure, and low soil organic matter content in this area.…”
Section: Introductionmentioning
confidence: 99%